Carbon Dots-based Antifungal Coating Film Against Pathogens Colletotrichum sp. for Active Coating Application of Mango - Safitri, Idayu; Sugiarti, Sri; Darmawan, Noviyan (Science and Technology Indonesia, 2024)
Mangos are one of horticultural products that are leading the Indonesian agricultural industry. Simple post-harvest handling leads to high damage. The most common causes is anthracnose disease caused by Colletotrichum sp. Therefore, it’s necessary to modify the existing methods in postharvest handling such as coating. Adding active agents such as carbon dot (CD) in coating material to prevent anthracnose from growing and shorten the shelf life. This study aims to investigate the applicability and antifungal properties of CD as a composite coating. CDs were synthesized using chitosan as the carbon source in a one-pot hydrothermal technique. The CDs have blue-emitting luminescence caused by the functional group at the surface of CD. The CDs were used to prepare chitosan/pectin (Chi/Pec)-based composite coatings. The addition of CDs increased the viscosity and density of composites, increased the blue-emitting luminescence, and showed potential antioxidant activity. The CDs and composite coatings exhibited high antifungal activity against Colletotrichum sp. by agar well diffusion method and were classified as very strong antifungal agents. The chitosan/pectin/CDs-coating effectively reduced the growth of black spots on the surface of mangos and increased the fruit shelf life of the fruit by 24 days. The CDs are evidently safe, affordable, and value-added nanomaterials that can be used to prepare active packaging applications.